Manajemen Pendidikan Non-formal dalam Meningkatkan Kualitas Pendidikan Studi Kasus di Kumon Adi Sucipto Pejarakan Ampenan Kota Mataram - Sukmawati, Sukmawati; Yakin, Nurul; Citriadin, Yudin (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
Non-formal education serves as a tool for training and developing human resources to enable individuals in need of education to acquire the knowledge, skills, attitudes, and competitiveness they require. In addition to formal education, after-school learning is crucial for building future-ready people resources, which will be the cornerstone of Indonesia's development. The purpose of this study is to determine how Kumon raises student learning standards. In this qualitative case study that included income analysis, research informants included three student parents, two tutors, and one supervisor. The data for this study was gathered through observation, interviews, and documentation. The results of this investigation show that the Kumon approach, when used independently and at suitable discount rates, enhances.